Aftershocks Economic Crisis and Institutional Choice - Hemerijck, Anton (WRR, 2009)
Aftershocks was written in the midst of the deepest economic crisis since the Great Depression. Although it would be premature to presume to identify the repercussions of the crisis, it is clear that it will have profound aftershock effects in the political, economic, and social spheres. The book contains essays based on semi-structured interviews with leading scholars, European politicians and representatives from the world of business. They reflect on the origins of the crisis as well as the possible social, economic, and political transformations it may engender.